A Novel RELA Truncating Mutation in a Familial Behçet's Disease–like Mucocutaneous Ulcerative Condition. Issue 3 (15th February 2021) - Adeeb, Fahd; Dorris, Emma R.; Morgan, Niamh E.; Lawless, Dylan; Maqsood, Aqeel; Ng, Wan Lin; Killeen, Orla; Cummins, Eoin P.; Taylor, Cormac T.; Savic, Sinisa; Wilson, Anthony G.; Fraser, Alexander
Abstract : Objective: Monogenic Behçet's disease (BD)–like conditions are increasingly recognized and to date have been found to predominantly involve loss‐of‐function variants in TNFAIP3. This study was undertaken to identify genetic and pathobiologic mechanisms associated with a BD‐like mucocutaneous ulcerative syndrome and neuromyelitis optica (NMO) occurring in 3 generations of an Irish family (n = 5 cases and 5 familial controls). Methods: Whole‐exome sequencing was used to identify potential pathogenic variants in affected family members and determine segregation between affected and unaffected individuals. Relative v‐rel reticuloendotheliosis viral oncogene homolog A (RELA) expression in peripheral blood mononuclear cells was compared by Western blotting. Human epithelial and RelA −/− mouse fibroblast experimental systems were used to determine the molecular impact of the RELA truncation in response to tumor necrosis factor (TNF). NF‐κB signaling, transcriptional activation, apoptosis, and cytokine production were compared between wild‐type and truncated RELA in experimental systems and patient samples. Results: A heterozygous cytosine deletion at position c.1459 in RELA was detected in affected family members. This mutation resulted in a frameshift p.His487ThrfsTer7, producing a truncated protein disrupting 2 transactivation domains. The truncated RELA protein lacks a full transactivation domain. The RELA protein variants were expressed at equal levels in peripheral mononuclear cells. RelA −/− mouse embryonic fibroblasts (MEFs) expressing recombinant human RELAp.His487ThrfsTer7 were compared to those expressing wild‐type RELA; however, there was no difference in RELA nuclear translocation. In RelA −/− MEFs, expression of RELAp.His487ThrfsTer7 resulted in a 1.98‐fold higher ratio of cleaved caspase 3 to caspase 3 induced by TNF compared to wild‐type RELA ( P = 0.036). Conclusion: Our data indicate that RELA loss‐of‐function mutations cause BD‐like autoinflammation and NMO via impaired NF‐κB signaling and increased apoptosis.